Numerical study of storm surge-induced coastal inundation in Laizhou Bay, China - Li, Zhao; Li, Shuiqing; Hu, Po; Mo, Dongxue; Li, Jian; Du, Mei; Yan, Jie; Hou, Yijun; Yin, Baoshu (Frontiers in Marine Science, 2022)
Storm surge inundation can induce great disasters in coastal regions, and Laizhou Bay (LZB), located in the Bohai Sea, is a bay that frequently experiences coastal storm flooding. In this study, we perform a numerical study of the effects of wind and waves on the storm surge-induced coastal inundation in the LZB using the coupled model ADCIRC+SWAN. Two historical typhoons (No. 9216 Typhoon Polly (TY9216) and No. 1909 Typhoon Lekima (TY1909)) are considered, wave effects in terms of wind-wave-induced surface stress and radiation stress are included, and two widely used wind data sources (CFS and ERA5) are used. The results indicate that the total inundation area and average inundation depth in the LZB during TY1909 are 10.70%-19.16% larger than during TY9216, and the CFS wind field reproduces a 14.31%-23.05% more intense inundation simulation than does the ERA5 wind field. The wave-induced surface stress plays the primary role in increasing the inundation area and average depth by up to 11.42%-18.50% and 5.82%-8.75%, respectively, and the wave-induced radiation stress also increases the inundation area and average depth by 3.80%-6.60% and 3.70%-4.57%, respectively. The results highlight the importance of considering wave effects in storm surge-induced coastal inundation simulations, and we demonstrate that the wave effects on the inundation area can be quite sensitive to the choice of wind field source.